Different energy storage techniques: recent advancements, applications, limitations, and efficient utilization of sustainable energy - Kumar, Raj; Lee, Daeho; Agbulut, Umit; Kumar, Sushil; Thapa, Sashank; Thakur, Abhishek; Jilte, R. D.; Saleel, C. Ahamed; Shaik, Saboor (SPRINGER, 2024)
In order to fulfill consumer demand, energy storage may provide flexible electricity generation and delivery. By 2030, the amount of energy storage needed will quadruple what it is today, necessitating the use of very specialized equipment and systems. Energy storage is a technology that stores energy for use in power generation, heating, and cooling applications at a later time using various methods and storage mediums. Through the storage of excess energy and subsequent usage when needed, energy storage technologies can assist in maintaining a balance between generation and demand. Energy storage technologies are anticipated to play a significant role in electricity generation in future grids, working in conjunction with distributed generation resources. The use of renewable energy sources, including solar, wind, marine, geothermal, and biomass, is expanding quickly across the globe. The primary methods of storing energy include hydro, mechanical, electrochemical, and magnetic systems. Thermal energy storage, electric energy storage, pumped hydroelectric storage, biological energy storage, compressed air system, super electrical magnetic energy storage, and photonic energy conversion systems are the main topics of this study, which also examines various energy storage materials and their methodologies. In the present work, the concepts of various energy storage techniques and the computation of storage capacities are discussed. Energy storage materials are essential for the utilization of renewable energy sources and play a major part in the economical, clean, and adaptable usage of energy. As a result, a broad variety of materials are used in energy storage, and they have been the focus of intense research and development as well as industrialization. This review article discusses the recent developments in energy storage techniques such as thermal, mechanical, electrical, biological, and chemical energy storage in terms of their utilization. The focus of the study has an emphasis on the solar-energy storage system, which is future of the energy technology. It has been found that with the current storage technology, the efficiency of the various solar collectors was found to be increased by 37% compared with conventional solar thermal collectors. This work will guide the researchers in making their decisions while considering the qualities, benefits, restrictions, costs, and environmental factors. As a result, the findings of this review study may be very beneficial to many different energy sector stakeholders.
Keywords: Solar energy; Energy storage; Thermal energy storage; Mechanical energy storage; Biological energy storage; Chemical energy storage; SOLAR AIR HEATER; PHASE-CHANGE MATERIALS; MICROBIAL FUEL-CELLS; THERMAL PERFORMANCE; PRESSURE-DROP; NATURAL-CONVECTION; MECHANICAL ENERGY; SIZE DISTRIBUTION; COLLECTOR SYSTEM; VISIBLE-LIGHT; Thermodynamics; Chemistry